Broadband ground-motion simulations by coupling regional velocity structures with the geophysical information of specific sites. Issue 145 (June 2021) - Wang, Xiang-Chao; Wang, Jin-Ting; Zhang, Lei; He, Chun-Hui
Abstract: Velocity structures are essential for deterministic numerical simulation of ground motions. However, accurate 3D velocity structures are often lacking for most regions. Even if 3D regional velocity structures are available, they may have poor resolution and differ significantly from the realistic situation in local areas. To deal with this issue, this paper proposes a method to improve the velocity structures in broadband ground motion simulations by coupling the accessible regional velocity structures with the local geophysical information. Specifically, the square areas around the sites of target in the regional velocity structures are modified according to the local geophysical parameters. To verify this proposed method, the 1994 Northridge earthquake is simulated with the spectral element method as a case study. A 3D velocity model and two 1D velocity models, coupled with the local geophysical parameters, are used in the ground-motion simulation. It is demonstrated that ground motion simulations with the combination of regional velocity structures and local geophysical information can generally generate broadband ground motions that have a fair or good fit to the records. Therefore, the proposed method makes it promising to apply deterministic numerical simulations to earthquake engineering in regions without accurate velocity structures. Highlights: We propose a method to improve ground-motion simulations by coupling velocity structures with local geophysical information. The simulated ground motions of the 1994 Northridge earthquake are significantly improved by the proposed method. This method can broaden the applicability of ground-motion simulations to regions lacking accurate 3D velocity structures.